Ultrasound-Assisted-Extraction (UAE) of Phenolic Compounds from Bamboo Shoot and Its Potential Source of Anti-Inflammatory Agents for Gout Treatment - Nur Aqilah Zawani Mustaffa; Sity Aishah Mansur; Angzass Sari Mohd Kassim (Progress in Engineering Application and Technology, 2022)
The gouty arthritis is caused by the deposition of monosodium urates (MSU) crystals in joints and characterized by hyperuricaemia, a long-lasting abnormally high concentration of uric acids in the blood. Existing medications for gout arthritis such as Allopurinol are not always effective and may have side effects to the patients. Therefore, there has been increasing interest in looking for better medications to control gout, especially on compounds that can inhibit xanthine oxidase and cyclooxygenase. As such, green inhibitors from plants are widely investigated. This study utilised bamboo shoot as the source for green inhibitors. Soxhlet with UAE was employed for extraction and using different solvents, namely; water, methanol and methanol:water and varied sonication times (15-45 min), different yields of extract were collected. The capacity of the extracts to inhibit XO activity was assessed through XO assays with Allopurinol as the positive control. Then, the potential phenolic substances that may contribute to the effects were identified with HPLC. The results showed that the concentration of water-methanol extract with 30 minutes of sonication is 73% higher compared to without sonication and 71% higher than water-only extract. This could be due to water only allowing the extraction of polar components, hence lower content of extract. In agreement, the same method also displayed the highest value of XO inhibition (74.15%) which means it has better anti-inflammatory effect compared to other extracts. When comparison was made between the water-methanol extract and Allopurinol, the difference was only 12% in inhibiting XO activity. Sonication indeed enhances the extraction process where 30 minutes of sonication gives the optimum time for the extraction of anti-inflammatory compounds from bamboo shoots. In addition, the extracts may contain other anti-inflammatory components but ferulic acid and ellagic acid, as they were not detected by HPLC. The phenolic groups which contribute to anti-inflammatory activities are present in the bamboo shoots. It is hopeful that this study can provide preliminary data on the potential use of bamboo shoots as an anti-inflammatory source.